Modeling of soil reaction for seismic microzoning of building sites - Yu. Semenova (Геофизический журнал, 2015)
Protection against destructive earthquakes requires the reliable data on the behavior of soil during earthquakes. The methods of determination of resonance properties of the upper part of the geological environment section for the building site for the needs of earthquake engineering are discussed in this paper. The development of scientific views on the linear and nonlinear models of the geological environment are analyzes. The theoretical background of linear equivalent linear and nonlinear modeling of soil response to seismic effects of earthquakes is considered. The advantages and disadvantages of these methods and the criteria for their applicability are analyzes. Also we presented and analyzed the results of a linear, equivalent linear and nonlinear modeling of the reaction of real ground layer under the actual construction site in Kiev on different levels of earthquakes.